Writing the field recording sound, word, environment - Benson, Stephen 1969-; Montgomery, Will ca. 20./21. Jh (Edinburgh University Press, 2020)
The 11 essays collected here take the recent explosion of interest in field recording as the point of departure for an investigation of the sounded field in music and its relationship to literature and writing
Title from publisher's bibliographic system (viewed on 12 Nov 2020)
Acknowledgements -- Introduction: writing the field recording / Stephen Benson and Will Montgomery -- Preface: "Field" / John Berger. -- Part 1 Opening the field : Fields, theory, field theory: John Berger and Manfred Werder define a field / Nicholas Melia -- The nondescript / Stephen Benson -- Text-score-text / Will Montgomery. -- Part 2 The poetics of the field : Rubies reddened by Rubies Reddening / Michael Pisaro -- Pitch...of inhabiting: thoughts on the practice of sound, poetry and Virno's "accustomed place" / Carol Watts -- Druids fielding questions: Eva-Maria Houben, Emily Dickinson and Charles Ives / Dominic Lash -- Field recording as writing: John Berger, Peter Gizzi and Juliana Spahr / Redell Olsen. -- Part 3 The field in practice : Bittern space, a siskin / Patrick Farmer -- Disquiet / Lisa Robertson -- Hedges / Daniela Cascella -- Stirrup notes: fragments on listening / Jonathan Skinner. Notes on contributors -- Index
Keywords: Sound recordings in literature; Field recordings; Aufsatzsammlung